Whole-genome sequencing of rough Brucella melitensis in China provides insights into its genetic features. Issue 1 (1st January 2020) - Yang, Xiaowen; Piao, Dongri; Mao, Lingling; Pang, Bo; Zhao, Hongyan; Tian, Guozhong; Jiang, Hai; Kan, Biao
ABSTRACT: Brucella spp. can cause the zoonosis brucellosis, which affects public health and safety and even economic development. B. melitensis has a smooth phenotype, while 28 B. melitensis isolates had a rough phenotype in 2018. In this study, rough phenotype detection and whole genome sequencing methods were used to analyze the genetic features of rough B. melitensis . A drug susceptibility test was also performed. The results showed that the rough B. melitensis strains originated from strains isolated in China rather than from foreign strains. Furthermore, an MS tree showed that 9 complexes to be epidemic in China. For the rough B. melitensis strains, expression of the metabolic function genes varied in the earlier stages of evolution compared to the cellular process and signalling function genes. Expression of some transcriptional regulatory factors also varied in the later stages of evolution, and compared to MFS transporter genes, ABC transporter genes varied in the earlier stages. Moreover, as there was no significant difference in rifampicin, doxycycline and streptomycin susceptibility between the smooth and rough B. melitensis strains, treatment of brucellosis was not affected by strain type. This study provided important information for understanding the genetics and evolution of rough B. melitensis in China.